1999
DOI: 10.1159/000018784
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary Approach to Palliation of Obstructive Jaundice Caused by a Central Hepatocellular Carcinoma

Abstract: Background/Aims: Obstructive jaundice due to intraductal tumour growth is a rare symptom in association with hepatocellular carcinoma (HCC). Methods: We report a 65-year-old white male who was admitted to our department with a 2-week history of progressive jaundice. At laparotomy, the liver showed advanced cirrhosis due to long-standing biliary obstruction. Cholangiography confirmed total obstruction of the main bifurcation of the hepatic duct by intraductal tumour growth. Combination treatment with surgical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
0
8
0
1
Order By: Relevance
“…When effective biliary drainage is achieved in patients with obstructive jaundice caused by HCC after an appropriate biliary drainage procedure, clinical outcomes, such as CTP class are affected, which means that they are able to receive additional treatment for HCC. It has been established that the mean survival of patients treated by biliary drainage alone ranges from 2.5 to 4.5 months and that the mean survival of patients treated using a combination of palliative therapies ranges from 8 to 13.4 months [5,14,16,29,30]. Furthermore, we found that an age of more than 63 years, ineffective biliary drainage, and no subsequent treatment for HCC, other than supportive care, were independent risk factors of mortality.…”
Section: Discussionmentioning
confidence: 54%
“…When effective biliary drainage is achieved in patients with obstructive jaundice caused by HCC after an appropriate biliary drainage procedure, clinical outcomes, such as CTP class are affected, which means that they are able to receive additional treatment for HCC. It has been established that the mean survival of patients treated by biliary drainage alone ranges from 2.5 to 4.5 months and that the mean survival of patients treated using a combination of palliative therapies ranges from 8 to 13.4 months [5,14,16,29,30]. Furthermore, we found that an age of more than 63 years, ineffective biliary drainage, and no subsequent treatment for HCC, other than supportive care, were independent risk factors of mortality.…”
Section: Discussionmentioning
confidence: 54%
“…For patients with unresectable icteric type of HCC, a combination of palliative treatments improves the patient's quality of life and possibly prolongs survival. Chen et al 59 12 Mean 3.9 (2-7) 3 ND ND Mean 8 (3-12) Lau et al 8 35 Median 2.5 (1-12) ND ND ND ND Hu et al 48 9 Mean 4.5 (2-9) 3 ND ND Mean 11 (9-13) Lauffer et al 60 ND ND ND ND 1 32 Huang et al 28 2 Mean 3 (2-4) 4 1 3 Median 13.4 (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) HCC, hepatocellular carcinoma; ND, no data obtained; TACE, transcatheter arterial chemoembolization.…”
Section: Discussionmentioning
confidence: 99%
“…59,[61][62][63][64][65] The mean survival using a combination of palliative therapies ranged from 8 to 13.4 months (Table 3). 8,28,48,59,60 There are no data on the use of local ablative therapy, either alone or in combination with other therapies, in the treatment of the icteric type of HCC in the published reports in medicine, although local ablative therapy is now increasingly used with good shortterm results in HCC. [66][67][68]…”
Section: Palliative Treatment For Icteric Type Of Hccmentioning
confidence: 99%
“…Tada and colleagues recommended preoperative biliary­drainage followed by transcatheter arterial embolisation for successful surgical treatment of icteric HCC [15]. Satisfactory palliation is possible with appropriate treatment for patients with unresectable tumours [3, 4, 16]. Thus in case no.…”
Section: Discussionmentioning
confidence: 99%